God and government : Martin Luther's political thought - Carty, Jarrett A., 1975- (McGill-Queen's University Press, 2017)
"Martin Luther (1483-1546) famously began the Reformation, a movement that shook Europe with religious schism and social upheaval. While his Ninety-Five Theses and other theological works have received centuries of scrutiny and recognition, his political writings have traditionally been dismissed as inconsistent or incoherent. God and Government focuses on Luther's interpretations of theology and the Bible, the historical context of the Reformation, and a wide range of writings that have been misread or misappropriated. Re-contextualizing and clarifying Luther's political ideas, Jarrett Carty contends that the political writings are best understood through Luther's "two kingdoms" teaching, in which human beings are at once subjects of a spiritual, inner kingdom, and another temporal, outer kingdom. Focusing on Luther's interpretations of theology and the Bible, the historical context of the Reformation, and a wide range of writings that have been misread or ignored, Carty traces how Luther applied political theories to the most difficult challenges of the Reformation, such as the Peasants' War of 1525, the Protestant resistance against the Holy Roman Empire, as well as social changes and educational reforms. The book further compares Luther's political thought to that of Protestant and Catholic political reformers of the sixteenth century. Intersecting scholarship from political theory, religious studies, history, and theology, God and Government offers a comprehensive look at Martin Luther's political thought across his career and writings."-- Provided by publisher.
Keywords: Luther, Martin, -- 1483-1546 -- Political and social views.; Luther, Martin, -- 1483-1546 -- Pensée politique et sociale.; Luther, Martin, -- 1483-1546; Luther, Martin -- 1483-1546; Political science -- History -- 16th century.; Two kingdoms (Lutheran theology); Science politique -- Histoire -- 16e siècle.; Deux royaumes (Théologie luthérienne); RELIGION -- Christianity -- Protestant.; Political and social views; Political science; Politisches Denken; 1500-1599; Electronic books.; History